Manuel de Falla’s Music Theater and Russian Art of the Early 20th Century (Meyerhold and Stravinsky) - I. A. Kryazheva (Ибероамериканские тетради, 2025)
The music theater of the Spanish composer Manuel de Falla, in particular, his most significant and representative work El Retablo de maese Pedro (Master Peter’s Puppet Show), is examined through the lens of the trends in theater relevant in early 20th century. Those include the diminishing role of the psychological theater and the developing conventional imagery of the representation theatre. Thus, Manuel de Falla’s Music Theater has clear parallels with the theater of the Russian avant-garde and with the work of artists such as Vsevolod Meyerhold and Igor Stravinsky. These similarities stem from the influence of various forms of ancient popular theater, fair and puppet shows, street «balagan» culture (balagans are temporary buildings where shows were set), which became subject of intense artistic reflection. Meyerhold pioneered the discovery of this new system of images as he presented his stage version of Aleksandr Blok’s «Balaganchik», revived the characters of the Italian comedy of masks on stage, as well as the openly playful nature of the action, and destroyed the invisible «fourth» wall separating the audience from the actors. Stravinsky’s ballet «Petrushka» is another example of how ballet embraces «balagan» culture. In this case, Stravinsky’s musical and theatrical aesthetic and style had a direct impact on the work of the Spanish composer. However, this influence manifests itself on a deeply individual level. On balance, the work of Manuel de Falla is explored as part of the most modern trends of his time.